Changing governance and management in higher education the perspectives of the academy - Locke, William; Cummings, William K.; Fisher, Donald (The changing academy--the changing academic profession in international comparative perspective, 2011)
External drivers are pressing for a more privatized approach to higher education and research, a greater reliance on technology and the more efficient use of resources. But many academics perceive these changes to be imposed from above with little consultation and an inadequate consideration of the beliefs and values that have traditionally guided academic work. The tensions between academic beliefs and contemporary drivers is more evident in certain national systems than in others, and within each system the tension raises particular issues. This book provides a framework for the analysis of recent changes in institutional governance and management in higher education and their impact on the academy and academic work globally. It pinpoints, as far as possible, the areas where recent change is perceived positively and negatively by academics themselves. Changing Governance and Management in Higher Education: The Perspectives of the Academy draws on the findings of an international study based on a common survey of academics in eighteen countries across five continents. The book opens with a chapter outlining the key issues, drivers and challenges that inform contemporary discourse around academic work and the profession in general. It then focuses primarily on national case studies, comparing changes in the top tier with the lower tiers of national systems, public and private institutions, and other differentiating factors as appropriate in each country, which include both mature and emerging higher education systems. The book concludes by proposing a series of generalizations about the contemporary status of governance and management of institutions of higher education